DIETARY INTERVENTIONS FOR SUPPORTIVE MANAGEMENT OF RHEUMATOID ARTHRITIS, SJÖGREN'S SYNDROME, AND SYSTEMIC LUPUS ERYTHEMATOSUS: A LITERATURE REVIEW - Błądek, Monika; Barszcz, Gabriela; Bębenek, Natalia; Drygała, Karolina; Wit, Sylwia; Frączkiewicz, Paulina; Harpula, Izabela; Ramotowski, Radosław; Bogdan, Justyna; Baljon, Benedykt; Brzezicki, Patryk (International Journal of Innovative Technologies in Social Science, 2026)
Rheumatological diseases, including rheumatoid arthritis (RA), Sjögren’s syndrome (SS), and systemic lupus erythematosus (SLE), affect millions worldwide. Standard therapy includes pharmacological treatment, physiotherapy, and, if needed, surgery; however, clinical improvement is not always achieved. Consequently, additional strategies such as dietary interventions are being explored. Chronic inflammation plays a key role in these diseases. Diets rich in anti-inflammatory components, particularly the Mediterranean diet, may reduce disease severity, symptoms, and inflammatory markers in RA and SLE. Intermittent fasting, ketogenic, and plant-based diets may also be beneficial. A literature review of PubMed using the terms “rheumatoid arthritis AND diet,” “Sjögren’s syndrome AND diet,” and “systemic lupus erythematosus AND diet,” alongside current rheumatology treatment guidelines, identified 30 relevant articles. Although evidence remains limited, positive findings support further research. Well-designed, evidence-based diets could complement pharmacological therapy, enhancing treatment outcomes and patient quality of life.